2016
DOI: 10.1302/2058-5241.1.000052
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in children with cerebral palsy

Abstract: Cerebral palsy (CP) children present complex and heterogeneous motor disorders that cause gait deviations.Clinical gait analysis (CGA) is needed to identify, understand and support the management of gait deviations in CP. CGA assesses a large amount of quantitative data concerning patients’ gait characteristics, such as video, kinematics, kinetics, electromyography and plantar pressure data.Common gait deviations in CP can be grouped into the gait patterns of spastic hemiplegia (drop foot, equinus with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(156 citation statements)
references
References 60 publications
3
116
0
15
Order By: Relevance
“…This makes sense since the widest movements involved in gait are ankle plantarflexion/dorsiflexion, and knee and hip flexion‐extension. Most of the gait pattern classifications are based on sagittal plane kinematics and many gait deviations observed and treated in children with CP occur in the sagittal plane . However, deviations in the transverse and frontal planes are also considered important in clinical decision‐making and intervention planning, and analyses in these planes could improve content validity of gait classifications …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes sense since the widest movements involved in gait are ankle plantarflexion/dorsiflexion, and knee and hip flexion‐extension. Most of the gait pattern classifications are based on sagittal plane kinematics and many gait deviations observed and treated in children with CP occur in the sagittal plane . However, deviations in the transverse and frontal planes are also considered important in clinical decision‐making and intervention planning, and analyses in these planes could improve content validity of gait classifications …”
Section: Discussionmentioning
confidence: 99%
“…The instrumented gait analysis (IGA) allows a precise quantification of gait characteristics, through objective data that cannot be appreciated visually or measured on a static physical examination . The IGA provides detailed information on four main types of data recorded simultaneously: spatiotemporal, kinematic, kinetic, and surface electromyography (sEMG) parameters . The IGA is often used in the assessment of ambulatory children with CP, for multiple purposes including the identification and understanding of gait deviations, the refinement of clinical decision‐making, and the evaluation and understanding of the effects of treatments on gait deviations .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for the differences between the AT and MT approach is that tuning all subtasks separately could be too complicated and time-consuming for clinical practice. The subtasks were related to common problems after neurological disorders [36][37][38][39][40]. They were chosen based on input from physical therapists and rehabilitation physicians who indicated that they would like to have more possibilities to tune the assistance than in other (commercially available) robotic gait trainers, which often only allow to change the general assistance for the whole gait cycle and multiple joints simultaneously [4,32].…”
Section: Possible Reasons For Differences Between the At And Mt Approachmentioning
confidence: 99%
“…По данным многочисленных источников, утверждают, что методы апоневротомии икроножной мышцы с рассечением межмышечной перегородки или частичной чрескожной тенотомии являются наиболее малотравматичными, функциональными и достаточно физиологичными методами коррекции эквинусной деформации при спастических формах ДЦП. Показанием к выполнению подобных вмешательств является изолированное контрагирование икроножной мышцы [19].…”
Section: эквинусная деформацияunclassified